The depression level effect on the QOL of patients with obstructive sleep apnea syndrome - Vicky Eko Nurcahyo; Donny Hendriyanto (Oto Rhino Laryngologica Indonesiana, 2020)
ABSTRACTBackground: Obstructive sleep apnea syndrome is one of the obstructive sleep disorders, which has a high prevalence. The neuropsychological impact will affect daily life activities, social life, and reduce the quality of life in patients with obstructive sleep apnea syndrome. Purpose: To find out the effect of depression level against the quality of life (QOL) on patients with obstructive sleep apnea syndrome. Method: Analytical observational study with cross sectional approach. The study sample was 30 patients with high risk of obstructive sleep apnea syndrome who came to Otorhinolaryngology Head and Neck Surgery Department of Dr. Moewardi Hospital, from February to April 2019. The samples were determined using the Modified Berlin Questionnaire, and had fulfilled the inclusion and exclusion criteria. The variables studied were measured using questionnaires, including the level of depression (Beck’s Depression Inventory-II) and quality of life (Sleep Apnea Quality of Life Index). Result: From 30 samples, there were 20 patients (66.7%) with moderate depression and 10 patients (33.3%) with severe depression. The mean QOL of patients with obstructive sleep apnea syndrome with moderate depression was 4.085±0.369, while with severe depression was 3.040±0.241. The Independent Samples t-test showed a statistically and clinically significant correlation between the level of depression and QOL patients with obstructive sleep apnea syndrome (95% CI=0.78-1.31; p=0.000; t=8.097). Conclusion: There was a significant effect of depression level on the quality of life of patients with obstructive sleep apnea syndrome. ABSTRAKLatar belakang: Obstructive sleep apnea syndrome merupakan salah satu gangguan bernapas saat tidur tipe obstruktif, yang memiliki prevalensi cukup tinggi. Gangguan neuropsikologis yang ditimbulkannya dapat mempengaruhi aktivitas kehidupan sehari-hari, kehidupan sosial, dan akan menurunkan kualitas hidup pada pasien obstructive sleep apnea syndrome. Tujuan: Mengetahui pengaruh tingkat depresi terhadap kualitas hidup pasien dengan obstructive sleep apnea syndrome. Metode: Penelitian observasional analitik dengan pendekatan potong lintang, yang dilaksanakan pada 30 pasien dengan risiko tinggi obstructive sleep apnea syndrome di Bagian Telinga Hidung Tenggorok Bedah Kepala dan Leher RSUD dr. Moewardi Surakarta. Subjek penelitian diambil berdasarkan Modified Berlin Questionnaire, dan memenuhi kriteria inklusi dan eksklusi. Variabel yang diteliti diukur menggunakan kuesioner, meliputi tingkat depresi (Beck’s Depression Inventory-II) dan kualitas hidup (Sleep Apnea Quality of Life Index). Analisis data dilakukan uji normalitas dengan uji Saphiro- Wilk. Jika data terdistribusi normal, uji hipotesis yang digunakan adalah Independent Samples t-test. Apabila data tidak terdistribusi normal maka dilakukan uji Mann Whitney. Nilai p<0,05 menunjukkan hasil yang signifikan. Hasil: Dari 30 sampel didapatkan 20 pasien (66,7%) dengan depresi sedang dan 10 pasien (33,3%) dengan depresi berat. Nilai rerata kualitas hidup pasien obstructive sleep apnea syndrome dengan depresi sedang didapatkan 4,085±0,369, sedangkan dengan depresi berat 3,040±0,241. Uji Independent Samples t-test menunjukkan adanya hubungan yang signifikan antara tingkat depresi dengan kualitas hidup pasien obstructive sleep apnea syndrome (IK 95%=0,78-1,31; p=0,000; t=8,097). Kesimpulan: Terdapat pengaruh tingkat depresi terhadap kualitas hidup pasien obstructive sleep apnea syndrome.